Organisation as communication: an empirical study of how the communication of impact investing is shaping its development in South Africa, Nigeria and Kenya - Malumba, Zanele (Research of GSB, 2018)
Over the years, investors demand greater transparency on how their funds are being invested. Whilst in the past it would have been enough for investment firms to seek primarily financial returns against all else; it is now becoming more common for investors to demand some form of positive impact above and beyond financial returns. In response to this, many strategies that seek more than just financial returns have been developed and impact investing being one such strategy. This research explores how fund managers and, or investors operating in the impact investment space communicate their practices to stakeholders in order to obtain an understanding of what they understand impact investing to be, and for those who may be investing for impact, understand the type of impact they seek to attain and also to appreciate how impact is being measured. The research findings suggest that despite much effort being put into the development of impact investing as a distinctive field, there are still a number of issues to iron out particularly with how companies communicate impact. The confusion and use of related terminology interchangeably is also an issue that is found to be detracting instead of adding to the development of the field.